Bright Future: The Role of Online Educational Technology in Empowering the Academic Advancement of Afghan Women - Nesari, Negina; Hosseini, Mahtab; Saberi, Nahid; Quraishi, Tamanna (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2025)
In Afghanistan, women face numerous socio-cultural and infrastructural barriers limiting their access to higher education. The advancement of online educational technology offers a promising avenue to empower Afghan women academically by providing flexible and accessible learning opportunities. This study explores the role of online education in enhancing academic access, confidence, and career prospects for women, while identifying the challenges and cultural perceptions that influence their participation. A quantitative research design was employed, surveying 160 female students from the Medical, Computer Science, Education, and Economics faculties at Vision Education and Research Institute. Data was collected through a structured questionnaire using a five-point Likert scale to assess participants’ experiences with online learning. Descriptive statistical analysis was conducted to examine trends in access, confidence, challenges, cultural acceptability, and perceived effectiveness. The results indicate that a majority of participants reported improved access to education and increased academic confidence through online learning. However, significant challenges such as unstable internet connections and limited access to suitable devices were prevalent. Cultural acceptance varied, with many respondents indicating general support but some experiencing resistance in their communities. Despite these obstacles, most participants perceived online education as effective in helping achieve their academic and career goals. In conclusion, online educational technology plays a crucial role in empowering Afghan women, though infrastructural and cultural barriers remain. Addressing these challenges through targeted interventions is essential to maximize the benefits of online learning and promote gender equality in Afghan higher education.